HUBUNGAN FAKTOR IBU DAN FAKTOR JANIN DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUMAH SAKIT UMUM DAERAH WATES - Ulfatuni'mah, Ulfatuni'mah; Theresia, Endah Marianingsih; Rahmawati, Anita (Poltekkes Kemenkes Yogyakarta, 2012)
The main cause of perinatal mortality aged 0-6 days were respiratory (37%). Asphyxia neonatorum caused by several factors, including maternal and fetal factors during pregnancy and childbirth. Objective: To determine the association between maternal factors (Preterm Rupture of membranes, long first stage, long second stage. chronic hypertension, hypertension in pregnancy and pre-eclampsia, birth pathological, hemorrhagic ante partum, and maternal infection) and fetal factors (pregnancy preterm, pregnancy post term, Gemelli, low birth weight, and congenital anomalies) and the incidence of asphyxia neonatorum. the research carried out by the cross-sectional design. Research location in Hospital Wates Kulon Progo District Yogyakarta. The study population was all women birthing in hospitals Wates Kulon Progo in January to December of 2011 amounted to 2246 mothers. Samples were taken by simple random sampling technique with 350 samples and the number of samples that have complete medical records as many as 336 samples. Data retrieved secondary data from medical records of patients. Analysis of the data using bivariate R.2.9.0 program with significance level 0,05. Results: maternal factors that have a significant association with the incidence of neonatal asphyxia are premature rupture of membranes the (p-value 0.00), long first stage (p-value 0.00). long second stage (p-value 0.00), and labor pathological (p-value 0.00). Fetal factors that have a significant association with the incidence of neonatal asphyxia are premature pregnancy (p-value 0.00) and low birth weight (p-value 0.01). While chronic hypertension, hypertension in pregnancy and pre-eclampsia, Hemorrhagic ante partum, infectious diseases, pregnancy post term, gemelli and congenital abnormalities have no significant association with the incidence of neonatal asphyxia. Conclusions: There is a significant association between maternal factors (premature rupture of membranes, long first stage, long second stage. and labor pathological) and fetal factors (premature pregnancy and low birth weight) with the incidence of neonatal asphyxia